2019
DOI: 10.5530/jyp.2019.11.62
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chamomile Tea on Anxiety and Depression in Cancer Patients Treated with Chemotherapy

Abstract: Objectives: Natural products such as chamomile have been used throughout the world for centuries as alternative medicines or functional food. Chamomile (Matricaria chamomilla L.) has been applied for centuries as an herbal remedy for treat various inflammatory conditions such as eczema, ulcers, gout, neuralgia and rheumatic pains. Materials and Methods: This study was a single blind clinical trial. The samples will be placed in two groups of intervention (55 people) and control (55 people) by convenient sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…All studies were published in English from 1991 to 2022. Seven studies were from Brazil, 35 - 41 6 from Iran, 42 - 47 2 from United Kingdom, 48 , 49 1 from Egypt, 50 1 from Finland, 51 and 1 from United States, 52 Regarding methodology, 15 studies were RCTs 35 - 37 ,39,41, 43 - 52 3 were non-RCT. 38 , 40 , 42 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were published in English from 1991 to 2022. Seven studies were from Brazil, 35 - 41 6 from Iran, 42 - 47 2 from United Kingdom, 48 , 49 1 from Egypt, 50 1 from Finland, 51 and 1 from United States, 52 Regarding methodology, 15 studies were RCTs 35 - 37 ,39,41, 43 - 52 3 were non-RCT. 38 , 40 , 42 …”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated the effect of chamomile on anxiety 44 , 48 , 49 , 1 study on depression. 44 In 2 RCTs, aromatherapy massage of the whole body using chamomile essential oil weekly over 3 consecutive weeks decreased anxiety levels in patients with cancer. 48 , 49 The findings of another RCT study by Ghamchini et al 44 showed that chamomile tea once a day for 2 weeks had no effect on the anxiety level in patients with cancer, but it decreased depression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, M. chamomilla showed antinociceptive effects against vincristine [199] and formalin [200] in animal models, showing its possible use to treat or attenuate negative side effects of chemotherapy. Clinical studies also showed the ability of M. chamomilla to reduce nausea [201], anxiety, and depression [202] in patients undergoing chemotherapy.…”
Section: Phyotherapeutical Applicationsmentioning
confidence: 99%